The city gate in ancient Israel and her neighbors : the form, function, and symbolism of the civic forum in the southern Levant - Frese, Daniel A., (Culture and History of the Ancient Near East;, 2020)
"In The City Gate in Ancient Israel and Her Neighbors, Daniel A. Frese provides a wide-ranging portrayal of one of the most prominent social institutions in the kingdoms of the southern Levant during the Iron II period: the use of the city gate as a hub for numerous and diverse civic functions. The book provides an up-to-date description of the architecture of gate complexes based on archaeological evidence, and a systematic description of the many functions of the gate seen in hundreds of texts from the Hebrew Bible and the broader ancient Near East. The final chapters of the book discuss the conceptual significance of gates in Israelite culture, based on idiomatic and symbolic gate terminology in the Hebrew Bible".